Dorsal root ganglion neurons recapitulate the traumatic axonal injury of CNS neurons in response to a rapid stretch in vitro - Adams, Alexandra A.; Li, Ying; Kim, Haesun A.; Pfister, Bryan J. (Frontiers in Cellular Neuroscience, 2023)
Neurons isolated from the central nervous system are often difficult to maintain in culture for extended periods of time and pose a challenge to studying the long-term effects of traumatic brain injury in vitro. Conversely, dorsal root ganglia (DRG) remain healthy in culture for much longer periods of time, can be isolated from adult sources, and can be myelinated in vitro. The known mechanisms of axonal degeneration from mechanical injury in TBI are similar in degenerative disease, ischemia and spinal cord injury. It is therefore possible that the mechanisms that result in axonal degeneration of isolated cortical axons after in vitro stretch injury are shared with injured axons from DRG neurons and their potential use as an in vitro model for TBI. The current study sought to characterize the differential responses of cortical and DRG axons to moderate and severe stretch injury in vitro. DRG and cortical axons immediately form undulations in response to severe injury, experience similar elongation and recovery within 20 minutes after the initial injury, and had a similar pattern of degeneration after over the first 24 hours after injury. Additionally, both types of axons experienced comparable degrees of calcium influx after both moderate and severe injury that was prevented through pre-treatment with lidocaine in DRGs. Severe injury also causes loss of expression of the sodium channel isoform 1.2 inactivation loop in DRG axons that is prevented by treatment with lidocaine or protease inhibitors. These findings suggest that DRG axons can model the early response of neurons to a rapid stretch injury.